Ktoś pomoże potrzebuje na teraz a nie rozumiem tego
![Ktoś Pomoże Potrzebuje Na Teraz A Nie Rozumiem Tego class=](https://pl-static.z-dn.net/files/dd3/d72da00ebf398351bde94b353d0b92e6.jpg)
Odpowiedź:
[tex]a)(3 {x}^{3} - 5 {x}^{2} + 7x - 1) - (4 {x}^{3} + 2 {x}^{2} - x + 5) = 3 {x}^{3} - 5 {x}^{2} + 7x - 1 - 4 {x}^{3} - 2 {x}^{2} + x - 5 = - {x}^{3} - 7 {x}^{2} + 8x - 6[/tex]
[tex]b)(2 {x}^{5} - 3 {x}^{4} + 2 {x}^{3} - x + 3) - ( {x}^{5} + 4 {x}^{3} + 2x - 1) = 2 {x}^{5} - 3 {x}^{4} + 2 {x}^{3} - x + 3 - {x}^{5} - 4 {x}^{3} - 2x + 1 = {x}^{5} - 3 {x}^{4} - 2 {x}^{3 } - 3x + 4[/tex]
[tex]c)( - 3 {x}^{2} + 5x - 1) \times (2x + 1) = - 6 {x}^{3} + 10 {x}^{2} - 2x - 3 {x}^{2} + 5x - 1 = - 6 {x}^{3} + 7{x}^{2} + 3x - 1[/tex]
[tex]d)(7 {x}^{3} + 2 {x}^{2} - 3x + 2)(3x + 2) = 21 {x}^{4} + 6 {x}^{3} - 9 {x}^{2} + 6x + 14 {x}^{3} + 4 {x}^{2} - 6x + 4 = 21 {x}^{4} + 20 {x}^{3} - 5 {x}^{2} + 4[/tex]
[tex]e)(2 {x}^{2} + 3x - 5)( - {x}^{2} + x + 2) = - 2 {x}^{4} + 2 {x}^{3} + 4 {x}^{2} - 3 {x}^{3} + 6x + 5 {x}^{2} - 5x - 10 = - 2 {x}^{4} - {x}^{3} + 12 {x}^{2} + x - 10[/tex]
[tex]f)(3 {x}^{3} + 2 {x}^{2} + 1)( - 2 {x}^{3} + x - 3) = - 6 {x}^{6} + 3 {x}^{4} - 9 {x}^{3} - 4 {x}^{5} + 2 {x}^{3} - 6 {x}^{2} - 2 {x}^{3} + x - 3 = - 6 {x}^{6} - 4 {x}^{5} + 3 {x}^{4} - 9 {x}^{3} - 6 {x}^{2} + x - 3[/tex]